Infection by Xanthomonas campestris pv.viticola under temperature increase and carbon dioxide concentrations - Conceição, Jaime Luiz Albuquerque; ANGELOTTI, FRANCISLENE; Peixoto, Ana Rosa; Ghini, Raquel (Comunicata Scientiae, 2018)
The experiments were carried out under controlled conditions to evaluate the impact of increased temperature and concentration of carbon dioxide on infection of Xanthomonas campestris pv viticola, the causal agent of bacterial canker in Vine seedlings. It proceeded the evaluation of the following epidemiological components: incubation period (PI), severity (SEV) and using that data were calculated the area under the disease progress curve (AUDPC). It used grape seedlings (Italia, Crimson Seedless, Sugraone and Selection 8) inoculated with bacterial suspension (108 CFU mL-1). The experimental design was completely randomized, factorial arrangement 4x4 (cultivar x temperature) and 4x2 (cultivar x carbon dioxide concentration) which was carried out twice. The data were subjected to variance analysis. Increasing temperature reduced bacterium’s incubation period with significant differences between genotypes. For Selection 8 and Crimson temperature increase caused enhancement on severity and AUDPC. For Seleção 8 the incubation period (PI) was extended from 7.93 to 30.18 days when the concentration changed from 390 to 770 µmol/mol. The increased CO2 concentration reduced AACPSD and SEV for Sugraone and Selection 8. The results show that the temperature and carbon dioxide (CO2) concentration of the air may have different effects on bacterial canker of grapevine.